Dysembryoplastic Neuroepithelial Tumors - Yeon-Lim Suh (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Dysembryoplastic neuroepithelial tumor (DNT) is a benign glioneuronal neoplasm that most commonly occurs in children and young adults and may present with medically intractable, chronic seizures. Radiologically, this tumor is characterized by a cortical topography and lack of mass effect or perilesional edema. Partial complex seizures are the most common presentation. Three histologic subtypes of DNTs have been described. Histologically, the recognition of a unique, specific glioneuronal element in brain tumor samples from patients with medically intractable, chronic epilepsy serves as a diagnostic feature for complex or simple DNT types. However, nonspecific DNT has diagnostic difficulty because its histology is indistinguishable from conventional gliomas and because a specific glioneuronal element and/or multinodularity are absent. This review will focus on the clinical, radiographic, histopathological, and immunohistochemical features as well as the molecular genetics of all three variants of DNTs. The histological and cytological differential diagnoses for this lesion, especially the nonspecific variant, will be discussed.